Stoichiometric controls of soil carbon and nitrogen cycling after long-term nitrogen and phosphorus addition in a mesic grassland in South Africa. (August 2019) - Schleuss, Per-Marten; Widdig, Meike; Heintz-Buschart, Anna; Guhr, Alexander; Martin, Sarah; Kirkman, Kevin; Spohn, Marie
Abstract: Terrestrial ecosystems have experienced rising nitrogen (N) inputs during the last decades with consequences for belowground carbon (C) and N dynamics. This study investigates how long-term N and phosphorus (P) additions affect microbial community composition, and to what extent microbial homeostasis explains changes in different processes involved in soil C and N cycling in response to nutrient addition. We studied a 66-year-old nutrient addition experiment in a mesic grassland in South Africa, consisting of four different levels of N addition (0, 7, 14, and 21 g N m −2 yr −1 ) with and without P addition (0, and 9 g P m −2 yr −1 ). Despite strong changes in the microbial community (observed through 16S rRNA gene and ITS amplicon sequencing), the microbial biomass C:N ratio did not change. N addition decreased microbial N acquisition as indicated by reduced leucine-aminopeptidase activity, and increased microbial net N mineralization. In contrast, predicted relative abundances of functional genes involved in degradation of labile C compounds (e.g. cellulose, hemicellulose, and chitin) as well as β-glucosidase and N-acetylglucosaminidase activities increased with elevated N availability. In combination, this pointed to a more intensive investment of microorganisms into C acquisition upon N addition. In contrast, N addition and associated soil acidification decreased microbial biomass and respiration and altered the community composition with prokaryotes being more affected than fungi. Nitrogen addition increased the relative abundance of gram-positive over gram-negative bacteria and favored taxa with low genome-size. Taken together, our findings support the concept that C and N cycling processes can be explained by the property of the soil microbial community to keep the element ratio of its biomass constant and by its reaction to soil acidification. Our findings suggest that predicted elevated N inputs might largely shape soil C and N cycling because the soil microbial community adjusts metabolic processes, which allows it to maintain its biomass stoichiometry constant. Graphical abstract: Image 1 Highlights: N (and P) additions affected the microbial community but not their C:N stoichiometry. Long-term N addition changed processes involved in C and N cycling. Abundance of genes involved in the C cycle increased with elevated N availability. Microbes invested less into peptidases and increased net N mineralization. N addition and associated soil acidification reduced C mineralization rates.